The Integrated Information System Implementation Strategy in Korlantas Polri Based on the Zachman Framework Approach - Rachmi Azanisa Putri; Panca Hadi Putra; Ryan Randy Suryono (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Traffic Police Corps (Korlantas Polri) is the executor of the main duties of the Indonesian National Police in the areas of security, safety, order and smooth traffic. Korlantas has some information that can be accessed by the public, namely information on congestion, accidents, traffic flow status, vital objects, road conditions, data and visual images from CCTV, public service conditions, and traffic infrastructure. However, these data are stand alone and not integrated with their respective applications and systems. The purpose of this study is to analyze the strategy for implementing an integrated information system at Korlantas Polri and what steps can be taken to integrate the existing system. This study uses the Zachman Framework which is adapted to Enterprise Architecture Planning (EAP) and qualitative data collection methods by interviewing stakeholders who are involved in managing information systems at Korlantas Polri. The results obtained are the need for a data warehouse by implementing an AI based integrated database system, Geospatial Information System, Business Intelligence and DSS, as well as Smart Visualization to visualize existing data. Then standardize the need for equipment and support for improving the ability of personnel in the IT field.